An Overview of Neoplasia in Captive Wild Felids in Southern Italy Zoos - d'Aquino, Ilaria; Piegari, Giuseppe; Casciaro, Silvia Mariagiovanna; Prisco, Francesco; Rosato, Guido; Silvestre, Pasquale; Degli Uberti, Barbara; Capasso, Michele; Laricchiuta, Piero; Paciello, Orlando; Russo, Valeria (Frontiers in Veterinary Science, 2022)
The aim of this study was to evaluate the frequency of neoplasms in captive wild felids in Southern Italy zoos over a 13-year period (2008–2021) and to investigate macroscopic and histologic tumor findings in these animals. A total of 24 cases were necropsied, 9 males and 15 females, with age ranging from 6 to 19 years, including 12 tigers (Panthera tigris), 7 leopards (Panthera pardus), 4 lions (Panthera leo), and 1 black jaguar (Panthera onca). Diagnosis of neoplasm was made in 14/24 cases (58.3%). Tumors diagnosed were two cholangiocarcinomas, two hemangiosarcomas of the liver, two uterine leiomyomas, a renal adenocarcinoma, an adrenal gland adenoma, a thyroid carcinoma, an oral squamous cell carcinoma, an osteoma, a meningioma, a mesothelioma, an esophageal leiomyosarcoma, a muscoloskeletal leiomyosarcoma and a thyroid adenoma. The malignant and benign tumors were 62.5% and 37.5%, respectively. Among malignant tumors, no metastasis was observed in 50% of cases; in 10% of cases metastasis involved only regional lymph nodes; and distant metastases were found in 40% of cases. Based on our findings, the liver was the most frequent primary tumor site (25%). The high rates of malignant and widely metastatic neoplasms suggest the importance of active monitoring and management of neoplasia in these threatened and endangered species.